Sun Pin military methods - Sun, Bin, active 4th century B.C (History and warfare, 1995)
The enormous recent popularity in America of Sun-tzu's Art of War has heightened awareness of the great Chinese tradition of writing on theory and practice of war, and new generations of readers have.